Malondialdehyde as a marker of lipid peroxidation in acute myocardial infarction patients - Shilpa H D; Anita R Bijoor (MRIMS Journal of Health Sciences, 2013)
Background: There is growing evidence that increase in free radical production and impaired antioxidant activity is important in the pathogenesis of acute myocardial infarction(AMI).increased lipid peroxidation is thought to be a consequence of lipid peroxidation which occurs when the dynamic balance between prooxidant and antioxidant mechanism is impaired. Malondialdehyde (MDA) is one of the most frequently used indicators of lipid peroxidation. It is one of the several byproducts of lipid peroxidation processes. Objective: The objective of this study was to evaluate the role of lipid peroxidation through measuring the MDA levels in cases of AMI and also to find out the changes in the levels of MDA through the course of the disease. Methods: A total of 30 patients were eligible for the study who met the inclusion and exclusion criteria. Blood sample was collected from these patients on the day of admission (day 0), 12-30 hrs after collecting the first sample (day 1), and 35-54 hrs after collecting the second sample (day 2). The patients were followed up to their discharge. MDA levels were estimated in the plasma by thiobarbituric acid (TBA) method. Results: This study showed a statistically significant increase in the MDA levels during the course of the study. Conclusion: There is clear evidence from this study and various other studies that there is a definite increase in the lipid peroxidation products in the event of AMI.Whether These changes, primary or secondary to the event, have any bearing on the prognosis of the patient and whether MDA can be used as a prognostic marker have to be investigated further.